The Application of Taiso Radio Gymnastic in Improving Gross Motor Ability of Children Aged 5-6 Years - Hardasari, Resta; Diana, Diana (Jurusan PGPAUD FIP UNNES, 2020)
The objective of this study was to obtain the data on the improvement of gross motor ability of children aged 5-6 years with taiso radio gymnastics. This research was included in the experimental research type. The population in this study were children aged 5-6 years at RA Diponegoro Kertanegara, Purbalingga. The respondents in this study were 33 children. The method of data collection in this study was the observation instrument of gross motor ability of children aged 5-6 years. Then the method of data analysis used were descriptive and hypothesis testing with Paired Sample t-Test. The results of this study indicated that the gross motor ability of children aged 5-6 years after being given treatment which was in the form of Taiso Radio gymnastics from an average of 92.91 to an average of 106.48. This was given a pretest treatment of gross motor ability of children aged 5-6 years in the fair category with a percentage index of 12.12% and a good category with a percentage index of 87.88%. After being given treatment (posttest) there was an increase in gross motor ability of children aged 5-6 years into a good category with a percentage index of 81.81% and a very good category with an achievement index of 18.19%. Therefore, taiso radio exercise is effective in increasing gross motor ability of children aged 5-6 years. Based on the results of the Paired Sample t Test calculation, the researcher obtained values -table > count > table, which was (-14.544 < -2.036 or 14.544 > 2.036), with sig = 0,000, so that was rejected and was accepted. It meant that there were differences in the gross motor ability of children aged 5-6 years after being applied to Taiso Radio gymnastics. The difference can be seen from the value of sig 2 tailed <0.005 which was 0,000.